The Flux of Select NSAIDs through Silicone Membranes from Mineral Oil - Paul S. Mertz; Kenneth B. Sloan (MDPI AG, 2014)
Here we report the experimental log maximum fluxes of n = 9 non-steroidal anti-inflammatory drugs (NSAID) through silicone membranes from the lipid mineral oil (experimental (Exp.) log JMPMO) and correlate those Exp. log JMPMO values with their experimental log maximum fluxes through human skin in vivo from mineral oil (Exp. log JMHMO). The correlation was only fair (r2 = 0.647) for n = 9 but improved dramatically if Nabumetone was removed from the correlation (n = 8, r2 = 0.858). Non-linear regression of the n = 8 Exp. log JMPMO values as the dependent variable against their log solubilities in mineral oil (log SMO) and in pH 7.4 or 1.0 buffers (log S7.4 or S1.0, respectively), and their molecular weights as independent variables in the Roberts-Sloan (RS) equation gave a new set of coefficients for the independent variables in RS. Those coefficients have been used to calculate log JMPMO values which have been correlated with the Exp. log JMPMO values to give r2 = 0.911 if log S7.4 and r2 = 0.896 if log S1.0 were used as aqueous phases. Thus, silicone membranes appear to be good surrogates for predicting flux through human skin if the vehicle is a lipid such as mineral oil.